1995
DOI: 10.1126/science.7716550
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Interhelical Electrostatic Interactions in the GCN4 Leucine Zipper

Abstract: The dimerization specificity of the bZIP transcription factors resides in the leucine zipper region. It is commonly assumed that electrostatic interactions between oppositely charged amino acid residues on different helices of the leucine zipper contribute favorably to dimerization specificity. Crystal structures of the GCN4 leucine zipper contain interhelical salt bridges between Glu20 and Lys15' and between Glu22 and Lys27'. 13C-nuclear magnetic resonance measurements of the glutamic acid pKa values at physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
173
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(187 citation statements)
references
References 46 publications
12
173
0
2
Order By: Relevance
“…Heterospecificity of helix pairing can be engineered into coiled coils by taking advantage of electrostatic repulsions in homomeric structures (termed ''negative design''), 18 electrostatic attractions in heteromeric structures, or both. [19][20][21] It is likely that charge repulsion plays a role in destabilizing the ecE and ecK homotetramers since, in both cases, the peptides are largely unfolded (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Heterospecificity of helix pairing can be engineered into coiled coils by taking advantage of electrostatic repulsions in homomeric structures (termed ''negative design''), 18 electrostatic attractions in heteromeric structures, or both. [19][20][21] It is likely that charge repulsion plays a role in destabilizing the ecE and ecK homotetramers since, in both cases, the peptides are largely unfolded (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the crystallographic structure, stabilizing interactions between oppositely charged ion pairs appear to be greater than destabilizing interactions between like charged residues, thus contributing to the overall stability of the folded dimer (O'Shea et al, 1989;Lumb et al, 1994). Recently, however, Lumb and Kim (1995) have observed that the charge-charge interaction between Lys 15 and Glu 2 0 might be actually destabilizing at the salt condition of their studies (150 mM NaCI), judging by the observed stabilization after replacing the Glu residue by Gln.The existence of stabilizing or destabilizing electrostatic effects can be evaluated by measuring the salt dependence of the stability of the coiled coil. In this paper, the dependence of the thermodynamic parameters on the concentration of different salts was investigated by high-sensitivity differential scanning calorimetry.…”
mentioning
confidence: 93%
“…However, the contributions of ionic interactions between charged end groups remains controversial . NMR measurements of pK, shifts of glutamates involved in ion pairs in the GCN4 structure suggest that the net contributions of interchain Glu-Lys electrostatic interactions to coiled-coil stability are either insignificant or slightly destabilizing (Lumb & Kim, 1995). The relative and absolute contributions of attractive and repulsiveg-e' ionic interactions are also clearly dependent on solution conditions (Monera et al, 1994;Yu et al, 1996).…”
mentioning
confidence: 99%